SUBJEK PENDIDIKAN DALAM KAJIAN TAFSIR SURAT AL-ANFAL AYAT 27 - Hafid Hafid (Qolamuna : Jurnal Studi Islam, 2020)
Abstract In this article, the focus is on discussing and examining the terminology of the subject of education in terms, objectives and content or educational material in the perspective of the Qur'an. Descriptive approaches and library research related to the subject of education in the perspective of the Qur'an include Imaniyah, khuluqiyyah, Jismiyah, Al-aqliyah wa al nafsiyah and Almihna. The Qur'an expresses the term education with the words tarbiyah and taklim. The content in the letter al-Anfal verse 27 teaches that the principal is a mandate from Allah SWT given to humans. As the head of the school, the principal has the task of managing various affairs in the school. Schools as formal institutions managed by the government and the community are the most likely places for a person. Keywords: Subject, Education, Q.S An-Nahl.